Manufacturing Organic Embryo Red Rice using Sugawa Machine at Lombok Kulon, Wonosari Subdistrict Bondowoso Regency, East Java - Rohimatush Shofiyah; Mochamad Alfan; Wiwik Suharso (OJS Universitas Muhammadiyah Gresik, 2020)
Gapoktan Al-Barokah of Lombok Kulon, Wonosari Subdistrict, in Bondowoso Regency has started milling organic rice using husking machine thus produced raw red rice. Raw red rice is rice grain that has its husks removed. The study established that raw red rice is actually covered by hard husk which contains Phytic Acid that could obstruct nutrition absorption to the body. Other drawbacks from raw red rice is that soaking is required before cooking, the texture of the cooked rice is hard to eat, and its nutrition is difficult to digest. These make it less favorable among society therefore it is not in a good sale so far, resulting in low revenue of the organic rice farmers. Therefore, this program was initiated to enrich the quality of red rice products through adding a step into the milling process which is milling using sugawa machine to remove the hard husks. The final product expected from the program was organic embryo red rice that is easy for cooking, soft textured cooked rice, and digestable rice in order to increase the chance of optimal nutrition absorption to the body. Among several solutions offered in the program include supplying and testing a milling machine, production training and guidance, socializing and marketing. The first solution administered was supplying and testing a Sugawa machine to mill raw rice into embryo red and brown rice. Then, it was followed by providing a Sugawa pressure cooker tool to mix derived product from the materials used such as embryo rice and bran, that is embryo porridge and bran cereal. The training conducted in the program contains guidance for applying the SOP of producing embryo rice and its derivatives. While socialization was administered specifically to the board and partners of Gapoktan Al-Barokah, village government, field trainers, and muspika (council for local government) of Wonosari aiming to achieve a collective and sustainable movement, as well as a group of patients of degenerative illnesses from Community Health Center of Wonosari. Finally, it was followed by marketing that was performed during the socialization by providing samples of embryo red rice, embryo brown rice, and its derivatives. The embryo rice was packaged in a 1kg-vacuum bag, labelled with Botanik Beras Embrio Merah and Botanik Beras Embrio Coklat and thereby distributed to nearby stores around Wonosari subdistrict area.